ANALISIS TINGKAT KEMANDIRIAN KEUANGAN DALAM MENDUKUNG PEMBANGUNAN PADA KABUPATEN KONAWE - Nurjanna Nurjanna (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2017)
This study is to find out whether the financial performance of Regional Government of South Konawe Regency in managing regional finances based on financial ratio of Regional Revenue and Expenditure Budget (APBD) during fiscal year 2013 - 2015. The method of data processing analysis used in this study is Descriptive analysis using the ratio of Regional Financial Independence, Effectiveness and Efficiency Ratio, Activity Ratio and PAD Growth Ratio. Data analysis techniques used in this study are the financial ratio at Regional Budget (APBD) South Konawe District Budget Year 2013- 2015. Based on the calculation and analysis of Regional Financial Capability can be concluded, that the condition of financial capacity Kab. Konawe South is still not ideal. Judging from the calculation of share and growth to the Budget Summary of Revenue and Expenditure District. Konawe Selatan Fiscal Year 2013 to 2015, the data obtained Share of 4.25% and Growth of 16.78%, so the position Kab. South Konawe is in quadrant II which means to be in condition not yet ideal.